The Constitutionality of the Mar Menor as a legal person: an anomalous solution in Spanish Law and of questionable protective effectiveness (Revista Española de Estudios Agrosociales y Pesqueros, 2025)
The purpose of this study is to provide a critical analysis of the arguments put forward by the Constitutional Court in Judgment 142/2024 to uphold the constitutionality of Law 19/2022, which grants legal personality to the Mar Menor and its watershed. The study examines the arguments presented in the constitutional challenge filed by the VOX parliamentary group against the entirety of Law 19/2022, which confers legal personality on the Mar Menor and its basin. Each of the four grounds summarized in the judgment is analyzed in detail, including the reasons why the Plenary of the Constitutional Court dismissed them, as well as the critical considerations expressed in the dissenting opinion of the judgment, signed by five of the twelve magistrates that made up the Plenary. In addition, this study offers a critical reflection on the legal-environmental paradigm shift promoted by the Law and endorsed by the Constitutional Court.
Keywords: Mar Menor; legal personality of the ecosystem; environmental law; Law 19/2022; Constitutional Court Judgement 142/2024; administrative inaction; institutional coordination; anthropocentrism and ecocentrism; legal status of the Mar Menor